2014
DOI: 10.1073/pnas.1315542111
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin (orexin) facilitates reward by attenuating the antireward effects of its cotransmitter dynorphin in ventral tegmental area

Abstract: Hypocretin (orexin) and dynorphin are neuropeptides with opposing actions on motivated behavior. Orexin is implicated in states of arousal and reward, whereas dynorphin is implicated in depressive-like states. We show that, despite their opposing actions, these peptides are packaged in the same synaptic vesicles within the hypothalamus. Disruption of orexin function blunts the rewarding effects of lateral hypothalamic (LH) stimulation, eliminates cocaine-induced impulsivity, and reduces cocaine selfadministrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
213
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 52 publications
17
213
2
Order By: Relevance
“…Moreover, AVP neurons contain not only AVP, but also other neurotransmitters, such as GABA and prokineticin 2 (Prok2) (Antle and Silver, 2005;Masumoto et al, 2006). Multiple transmitters in one neuronal type play differential roles in the neuronal transmission, as exemplified by orexigenic AgRP neurons in the hypothalamic arcuate nucleus (Krashes et al, 2013) and wake-promoting orexin neurons in the perifornical and lateral hypothalamus (Muschamp et al, 2014;Schö ne et al, 2014). Therefore, we considered it to be important to examine the role of neurons marked by AVP expression in the function of the SCN network.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AVP neurons contain not only AVP, but also other neurotransmitters, such as GABA and prokineticin 2 (Prok2) (Antle and Silver, 2005;Masumoto et al, 2006). Multiple transmitters in one neuronal type play differential roles in the neuronal transmission, as exemplified by orexigenic AgRP neurons in the hypothalamic arcuate nucleus (Krashes et al, 2013) and wake-promoting orexin neurons in the perifornical and lateral hypothalamus (Muschamp et al, 2014;Schö ne et al, 2014). Therefore, we considered it to be important to examine the role of neurons marked by AVP expression in the function of the SCN network.…”
Section: Introductionmentioning
confidence: 99%
“…Hcrt neurons activate these brain regions (Carter et al, 2012;Eggermann et al, 2001;Eriksson et al, 2001;Liu et al, 2002;Schone et al, 2012) through the co-release of Hcrt, glutamate (GLU) (Schone et al, 2012), and dynorphin (Eriksson et al, 2004;Li et al, 2014;Muschamp et al, 2014). Hcrt neurons are active primarily during wakefulness (Lee et al, 2005), and extracellular Hcrt levels are highest during awakening and periods of heightened emotionality (Blouin et al, 2013), consistent with a role in the regulation of arousal.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also indicated that activation of KORs inhibits and activation of OX1R activates the dopamine cells. Saturation of both receptors produces no net effect on dopamine cells, [20][21][22][23][24]suggesting that dysfunctions in orexin and dynorphin balance in the hypothalamus and dopaminergic reward system may be present in depression and cause anhedonia. Clinical research also highlights the links between Orexin / dynorphin and depression.…”
mentioning
confidence: 99%